Three surgical techniques using different energy sources for anatomical endoscopic enucleation of the prostate - Yi, Xin; Zhu, Gongliang; Zhu, Biyu; Zou, Junrong; Zhu, Jingyi; Zou, Xiaofeng; Zhang, Guoxi (Frontiers in Surgery, 2025)
Although transurethral resection of the prostate (TURP) remains the gold standard for the surgical treatment of benign prostatic hyperplasia (BPH), this approach is associated with a high recurrence rate and numerous postoperative complications. Recently, advancements in equipment and surgical techniques have led to the increased clinical application of anatomical endoscopic enucleation of the prostate (AEEP). The primary devices used in AEEP include bipolar plasma systems, holmium lasers, and thulium lasers. This article presents a narrative review evaluating the performance of these three energy sources in surgery and provides a comparative analysis of their advantages and disadvantages.